The irradiated human mandible: A quantitative study on bone vascularity. (December 2018) - Dekker, H.; Bravenboer, N.; van Dijk, D.; Bloemena, E.; Rietveld, D.H.F.; ten Bruggenkate, Chr.M.; Schulten, E.A.J.M.
Highlights: Irradiation decreases mandibular vascular density and vascular number. In local dosages exceeding 50 Gy, the proportion of smaller vessels decreases. With increased time after radiotherapy, the proportion of smaller vessels decreases. Abstract: Objectives: Hypovascularisation is thought to play an important role in the pathogenesis of osteoradionecrosis. The objective of this study was to assess the microvascular system in the irradiated mandibular bone marrow. Materials and methods: Mandibular bone biopsies were taken from 20 irradiated patients and 24 controls. Blood vessels were visualized using CD34 antibody stain to detect endothelial cells. The vascular density (VD) and vascular area fraction (VAF) were measured. Mean vessel lumen area, perimeter and diameter of the vessels were calculated for each vessel. A distinction was made between large and small vessels (cut-off point <400 µm 2 ). Results: Vascular density and vascular area fraction were lower in the irradiated group. The mean vascular perimeter and mean vascular diameter were higher in samples with a local radiation dose of ≥50 Gy, whereas the percentage of small vessels was lower. Larger vessel perimeter is associated with higher radiation dose. A longer interval between biopsy and radiotherapy is associated with a larger mean vessel perimeter and a lower percentage of small vessels. Conclusions: Radiation dosages higher than 50 Gy mainly affect the smaller vessels. With increased time after irradiation, the share of smaller vessels in the mandibular bone marrow seems to decrease. In search of the exact mechanisms of irradiation damage and osteoradionecrosis of the mandible, the role of the microvascular system in the mandibular bone marrow should be further explored.